1974
DOI: 10.1161/01.cir.49.5.968
|View full text |Cite
|
Sign up to set email alerts
|

The Adequacy of Subendocardial Oxygen Delivery

Abstract: SUMMARYThe coronary flow must increase if elevated myocardial oxygen demands are to be met adequately. This increased flow is achieved through coronary artery dilatation (autoregulation) but can reach the subendocardial region only during diastole (intramyocardial compressive forces are greatest in the subendocardium and therefore prevent its perfusion during cardiac contraction).4-7 When subendocardial vessels become maximally dilated, subendocardial flow will be determined by the coronary driving pressure (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…During the collection of aortic flow, time to peak pressure and the relaxation times at 10, 50, and 80% total relaxation (RT 10, RT 50 , and RT 80 , respectively) were measured from the pressure traces. Systolic and diastolic pressure time integrals (STI, correlating with myocardial energy expenditure (31)(32)(33)(34), and DTI, correlating with diastolic function and coronary perfusion (35)(36)(37)(38)(39)(40)(41)(42), respectively) were calculated by integrating the systolic and diastolic portions of the pressure waves.…”
Section: Measurement Of Left Ventricular Pressure Development In Vivo-mentioning
confidence: 99%
See 1 more Smart Citation
“…During the collection of aortic flow, time to peak pressure and the relaxation times at 10, 50, and 80% total relaxation (RT 10, RT 50 , and RT 80 , respectively) were measured from the pressure traces. Systolic and diastolic pressure time integrals (STI, correlating with myocardial energy expenditure (31)(32)(33)(34), and DTI, correlating with diastolic function and coronary perfusion (35)(36)(37)(38)(39)(40)(41)(42), respectively) were calculated by integrating the systolic and diastolic portions of the pressure waves.…”
Section: Measurement Of Left Ventricular Pressure Development In Vivo-mentioning
confidence: 99%
“…Previous studies have established that the DTI/STI ratio correlates closely with the blood supply to the subendocardium (37)(38)(39)(40)(41)(42). Because coronary perfusion occurs during diastole, a faster rate of relaxation would produce a longer duration of diastole, yielding deeper perfusion from the coronary arteries.…”
Section: Regulation Of Ctni Function By Restrictedmentioning
confidence: 99%
“…This progressive augmentation of coronary flow maintains overall myocardial oxygen delivery and occurs with a ~2-fold increase in MVO 2 and little/no change in myocardial oxygen extraction [10, 19, 34, 35, 47, 64, 67, 68]. However, evidence of enhanced myocardial lactate release and impairments to both sub-endocardial blood flow and cardiac contractile function have been reported with more severe reductions in hematocrit (≤ 10%) [1, 3, 37, 45, 64]. Earlier studies have suggested a role for reduced blood viscosity in the coronary response to anemia [5, 31, 33, 46, 62].…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrollable renal anemia has a negative effect on maintaining the balance in myocardial oxygen supply and demand. In an animal study, it was reported that in the presence of even mild anemia in dogs, electrocardiographic signs of ischemia and relative subendocardial underperfusion were observed with aortic stenosis—a typical situation in which myocardial oxygen demand is increased [31]. This means that the combination of anemia with increased oxygen demand, such as hypertension and/or volume overload, readily leads to an imbalance in myocardial oxygen supply and demand.…”
Section: Imbalance In Myocardial Oxygen Supply and Demandmentioning
confidence: 99%